Solanum sisymbriifolium Lam. - An Addition to the Flora of Jharkhand, India - Panda, S. P.; Sahu, H. K.; Sahu, A. K.; Subudhi, H. N. (Journal of the Bombay Natural History Society (JBNHS), 2014)
No abstract.